Peningkatan Kemampuan Komunikasi Anak Speech Delay Melalui Metode Bermain - Nurmayanti Nurmayanti; Atien Nur Chamidah (Jurnal Ners, 2026)
This study aims to: (1) examine the learning process through the play method in improving the communication skills of children with speech delay at Tunas Bangsa Kindergarten, East Kutai Regency; and (2) identify the outcomes of applying this method to enhance children's communication abilities. The study used a Classroom Action Research (CAR) approach combining qualitative and quantitative methods. This independent CAR involved the teacher as both the implementer and the researcher. The research was conducted to directly improve the learning process, particularly in addressing the low communication skills of children with speech development disorders. The subjects were 4 children with speech delay out of a total of 15 students in the class. The primary instrument was the researcher (human instrument). Data were collected through classroom observations, field notes describing teacher and student activities, tests (evaluations and final assessments) to measure progress in communication skills, and documentation of the children’s development during the learning process. The results show that the success indicators were met, with 60% to 75% of students showing positive engagement and enjoyment during play-based learning, and 75% to 80% achieving minimum to maximum levels of improvement. Additionally, there was a noticeable increase in the number of words and sentences used by children with speech delay, demonstrating that play-based media is effective in enhancing their communication abilities. This finding confirms that a fun, interactive, and child-centered learning approach can positively impact the language development of children with special needs.